«Kolchak and Pepeliaev in prison»: memories of M. A. Grishina-Almazova - D. I. Petin; M. M. Stelmak (Омский научный вестник: Серия "Общество. История. Современность")
This archaeographic publication is devoted to the military-political events in Irkutsk in mid-January–early February 1920 which played an important role in ending the Civil War in Siberia. The purpose of the work, using the example of a little-known and hard-to-reach source, the memoirs of M. A. Grishina-Almazova, is to present the last days of the key leaders of the anti-Bolshevik movement A. V. Kolchak and V. N. Pepelyaev. The publication is addressed to the researchers of the political everyday life of the Civil War, the White movement, the Red Terror, and those interested in the biographies of A. V. Kolchak, V. N. Pepeliaev, A. V. Timireva, M. A. Grishina-Almazova (Mikhailova)